Effect of Chilled Ageing Conditioning at 4°C in Lamb Longissimus Dorsi Muscles on Water-Soluble Flavour Precursors as Revealed by a Metabolomic Approach - Liqin You; Ruiming Luo (Journal of Food Quality)
The objective of this study was to investigate, by a metabolomic approach, the effects of chilled ageing conditioning at 4°C in lamb longissimus dorsi (LD) muscles on water-soluble flavour precursors. The results showed that the content of nucleotide degradation products significantly increased (P<0.05) due to the adjusted biosynthesis of alkaloids derived from histidine and purine from day 0 to day 4. Additionally, the content of glycolytic compounds significantly increased (P<0.05) due to enhanced glycolysis, and the content of organic acid increased (P<0.05) because of the altered tricarboxylic acid cycle (TCA) from day 0 to day 4. In addition, the content of total free amino acids significantly increased (P<0.05), owing to the altered biosynthesis of amino acids from day 4 to day 8. These results are significant proof that there were quantitative changes observed in lamb flavour precursors during chilled ageing.